Performance evaluation of space-grade FPGA architectures - Christian Spindeldreier and Buse Ustaoglu and Ulf Kulau and Jochen Rust (IEEE, 2024)
In this paper a comprehensive overview about State-of-The-Art Space-Grade FPGA and SoC-FPGA platforms from AMD, Microchip, NanoXlore and Frontgrade is presented. To this end, a resource-optimized LEON3 soft-core processor system is taken into account as a core design. For evaluation, resource utilization, achievable operating frequency, power consumption as well as radiation performance are taken into account. The results clearly point out the strengths and weaknesses of all space-grade FPGAs selected as well as it helps in the assessment and selection of the optimal candidate for upcoming space applications.
Keywords: Hardware Performance; LEON3; Space-Grade FPGA